The implications of Malaysian checkpoints and border agency on the Sabah royal Malaysian custom department's work culture - Ali Hasan Buglayan; Sulaiman Tahajuddin; Jasman Bandar (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2024)
Emotional intelligence and resilience are very important things in guaranteeing the survival and sustainability of an individual's career. However, this issue often occurs in both government and private sector careers. Failure to overcome this issue can disrupt the nature and perform optimally in the career world. JKDMS has gone through a drastic change process with the existence of MCBA which has caused a change in the organizational climate that aims to empower JKDMS's achievements. The impact of this transition will certainly affect emotional intelligence and resilience among members. The purpose of this study is to examine emotional intelligence and resilience among JKDMS members in the MCBA. Started with quantitative study first and then was supported by a qualitative study. Through the results of a quantitative study showing that the level of resilience and emotional intelligence are each at a high significant level. The findings of this quantitative study are supported by interview data that explains that MCBA provides a new scenario to the career world that increases enthusiasm and encouragement for them to show the quality and quality for them to achieve the target they want to achieve in the department. The implications of this study can provide a positive contribution to the career development and performance of JDKMS to a more outstanding level. practically the findings of this study can preserve the achievements of JKDMS.